Qatar’s Regulations – Striking a Balance between Protectionist Measures and Encouragement of Foreign Direct Investment (FDI) in Qatar - Thani, Maha K. Al (American Journal of Trade and Policy, 2022)
As part of its commitment to fostering economic prosperity and to further fortifying its already robust economy, Qatar has spearheaded several initiatives to attract Foreign Direct Investment (FDI). In doing so, however, Qatar must balance attracting investments from abroad while safeguarding its interests at home. This balance often becomes fragile as the same regulations imposed to offer protection to Qatari businesses (e.g., partial ownership and restricting investment to only a select few industries) often deter interests from abroad and raise barriers to entry. To restore this balance, Qatar has introduced various measures, including tax exemptions, free zones, and the use of commercial agents who are registered with the Ministry of Commerce and Industry (MOCI) to incentivize foreign investors and facilitate and stimulate the growth and diversification of its economy, while allowing the nation to protect its assets at home. This essay will argue that although Qatar’s regulation might discourage some investors, the law finds an appropriate balance between protecting Qatari interests and encouraging FDI.
Keywords: Commercial Law; FDI; National Vision 2030; Qatar